“WHAT DOES A WOMAN WANT?” EMBRACING THE GODDESS IN MEDIEVAL ROMANCE - Greene, Logan Dale (Revista Literatura em Debate, 2013)
This paper examines an archetype, or mytheme, that lies at the heart of a medieval tale, Chaucer’s Wife of Bath’s Tale from The Canterbury Tales. Writers of the fourteenth century used classical mythology as a way of aligning themselves with a revered past and Celtic myth asa way of incorporating the pre-Christian heritage of magic. The mythic narrative employed often changed form to serve the author’s purpose. The Celtic archetype in the Wife’s Tale, an image of transformation, was transformed by Chaucer so that it contributed to the ongoing argumentsthroughout the Tales about marriage and the nature of women. One of the most compelling images in European mythology is the hero’s embrace of the goddess. This great moment is often represented as a mystical marriage, the hieros gamos, which was described by Carl Gustav Jungas the union of self and soul. This ancient story appears in many versions in medieval European literature, including Chaucer’s Wife of Bath’s Tale from the Canterbury Tales. It is tempting to read Chaucer’s Wife’s tale as a woman’s story: it is told by a female character and arguably bearssome relation to the psychology of that character; it is based on an offense done to a young woman; it features the magical hag as a central character; it demonstrates the significant political power of the queen’s court. However, the Wife’s tale derives from the ancient Celtic myth withits archetypal patterns for masculine development. This paper will explore the implications of the myths of the old hag, sometimes called the Loathly Lady, for Chaucer’s Wife’s tale as well as other medieval romances, and it will offer a reading that respects the masculine dynamic implicit in the mythic foundation.“O QUE A MULHER DESEJA?” – ABRAÇANDO A DEUSA NO ROMANCE MEDIEVALEste ensaio examina um arquétipo que é central a um conto medieval, “O Conto da Mulher de Bath”, de Os Contos de Cantuária, de Chaucer. Os escritores do século XIV usavam a mitologia clássica como um modo de se associar ao mito celta e a um passado reverenciado, de forma a incorporar uma herança pré-cristã. A narrativa mítica empregada freqüentemente trocava de forma para servir aos propósitos do autor. O arquétipo celta em “O Conto da Mulher de Bath”, uma imagem de transformação, foi mudada por Chaucer de forma a contribuir para os argumentos apresentados ao longo dos Contos sobre o casamento e a natureza das mulheres. Uma das mais interessantes imagens da mitologia européia é a do abraço do herói à deusa. Este grande momento é freqüentemente representado como um casamento místico, o hieros gamos, que foi descrito por Carl Gustav Jung como a união do eu e da alma. Esta história aparece em muitas versõesda literatura européia medieval, inclusive em “O Conto da Mulher de Bath”, em Os Contos de Cantuária de Chaucer. É tentador ler esse conto como uma história de uma mulher: é contado por uma personagemfeminina e tem relação com sua psicologia; é baseado numa ofensa cometida contra uma jovem mulher, tem como seu personagem central a velha e feia mágica e demonstra o significativo poder político da corte darainha. Contudo, “O Conto da Mulher de Bath” deriva de antigo mito celta, com seus padrões para o desenvolvimento masculino. Este estudo explora as implicações do mito da velha feia, algumas vezes chamada de Dama Repugnante, no conto de Chaucer e em outros romances medievais, e oferece uma leitura da dinâmica masculina implícita nesse mito fundacional.